2018
DOI: 10.1111/hepr.13230
|View full text |Cite
|
Sign up to set email alerts
|

Ratio between estimated glomerular filtration rates of creatinine and cystatin C predicts overall survival in patients with hepatocellular carcinoma

Abstract: The Scre/Scys ratio is associated with muscle mass and liver function. Furthermore, the eGFRcre/eGFRcys ratio could serve as a useful predictive marker for survival of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
(34 reference statements)
0
18
1
Order By: Relevance
“…The decrease in muscle strength is significantly more rapid than the concomitant loss of muscle mass (37). Tamai et al (15) described that the eGFRcre/eGFRcys ratio could be a useful predictive marker for survival in patients with hepatocellular carcinoma. As the relationship between dGFR and grip strength was clarified in the present study, the relationship between dGFR and the prognosis of liver disease should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in muscle strength is significantly more rapid than the concomitant loss of muscle mass (37). Tamai et al (15) described that the eGFRcre/eGFRcys ratio could be a useful predictive marker for survival in patients with hepatocellular carcinoma. As the relationship between dGFR and grip strength was clarified in the present study, the relationship between dGFR and the prognosis of liver disease should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cr-to-CysC ratio (Cr/CysC x100), the so-called sarcopenia index (SI), has been reported to be associated with a fair measure of muscle mass estimation among patients admitted in the intensive care unit and can modestly predict the time in hospital and 90-day mortality among patients who do not have acute kidney injury at the time of measurement (11). SI correlates with muscle volume in patients with critical illness (11,12), lung transplant candidates (13), patients with type 2 diabetes (14) and patients with hepatocellular carcinoma (15). Cr production is relatively constant when the muscle mass is stable.…”
Section: Indices Calculated By Serum Creatinine and Cystatin C As Prementioning
confidence: 99%
“…Moreover, we did not evaluate clinical data reflecting skeletal muscle volume loss. A recent study reported that the ratio between serum creatinine and serum cystatin C can be used as a surrogate for skeletal muscle and the ratio between estimated glomerular filtration rates of creatinine and cystatin C was independent predictor of survival in patients with HCC . Prospective large‐scale studies to overcome the above‐mentioned limitations and interventional studies to prevent sarcopenia are needed to improve prognosis in patients with HCC receiving TACE.…”
Section: Discussionmentioning
confidence: 99%
“…SI was calculated as follows: Cr / CysC ×100. CBMM was calculated using Cr, CysC, and BW according to the original report . The CBMM was calculated as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the sarcopenia index (SI): (serum creatinine [Cr] / serum cystatin C [CysC] × 100) was reported as a fair measure of muscle mass estimations among patients admitted to intensive care units, and it could modestly predict the hospitalization duration and 90‐day mortality rates among patients who did not have acute kidney injuries when the measurements were taken . SIs have been correlated with muscle volumes in patients with critical illnesses, lung transplant candidates, patients with type 2 diabetes, and patients with hepatocellular carcinomas . Additionally, a new calculated body muscle mass (CBMM) equation to estimate total body muscle mass using Cr and CysC levels was developed .…”
Section: Introductionmentioning
confidence: 99%